Revision of the Alycaeidae of China, Laos and Vietnam (Gastropoda: Cyclophoroidea) I: The genera Dicharax and Metalycaeus - Páll-Gergely, Barna; Hunyadi, András; Sáng, Đức Đỗ; Naggs, Fred; Asami, Takahiro (Zootaxa, 2017)
This is the first part of the revision of the Alycaeidae of China, Laos and Vietnam. Here we revise the species hitherto classified in Chamalycaeus Möllendorff, 1897 (genera Dicharax and Metalycaeus in this study). We show that no Chamalycaeus live in the region, and the alycaeid species of the investigated region can be classified into five genera: Alycaeus Baird, 1850, Dicharax Kobelt & Möllendorff, 1900, Dioryx Benson, 1859, Metalycaeus Pilsbry, 1900 and Pincerna Preston, 1907. We propose Dioryx dautzenbergi Páll-Gergely nom. nov. as a replacement name for Alycaeus (Dioryx) major Bavay & Dautzenberg, 1900, non Alycæus (Dioryx) granum var. major Godwin-Austen, 1893. Alycaeus anceyi Mabille, 1887, A. eydouxi Venmans, 1956, A. mouhoti L. Pfeiffer, 1862, A. rolfbrandti Maassen, 2006 and A. vanbuensis Bavay & Dautzenberg, 1900 are retained in Alycaeus. Alycaeus costulosa Bavay & Dautzenberg, 1912 and A. maolanensis Luo, Zhang & Zhuo 2009 were transferred to Pincerna. We examined newly collected specimens and the type specimens of all species with the exception of the following: A. elevatus Heude, 1886, A. expansus Heude, 1890, A. neglectus Heude, 1885, Chamalycaeus libonensis Chen, Li & Luo 2003, C. panshiensis Chen, 1989, C. tangmaiensis Chen & Zhang, 2001, C. zayuensis Zhang, Chen & Zhou, 2008. Fifteen new species are described as follows: Dicharax (?) abdoui Páll-Gergely, n. sp., Dicharax (?) alticola Páll-Gergely & Hunyadi n. sp., Dicharax (?) ellipticus Páll-Gergely n. sp., Dicharax (?) immaculatus Páll-Gergely n. sp., Dicharax bison Páll-Gergely & Hunyadi n. sp., Dicharax draco Páll-Gergely & Hunyadi n. sp., Dicharax imitator Páll-Gergely & Hunyadi n. sp., Dicharax microcostatus Páll-Gergely n. sp., Dicharax micropolitus Páll-Gergely & Hunyadi n. sp., Dicharax robustus Páll-Gergely & Hunyadi, n. sp., Metalycaeus (?) awalycaeoides Páll-Gergely & Hunyadi n. sp., Metalycaeus (?) ibex Páll-Gergely & Hunyadi n. sp., Metalycaeus laosensis Páll-Gergely n. sp., Metalycaeus oharai Páll-Gergely & Hunyadi n. sp., Metalycaeus (?) okuboi Páll-Gergely & Hunyadi, n. sp. A total of twelve names are synonymised with valid species. In this revision we payed special attention to conchological characters hitherto neglected, such as the fine sculpture of the embryonic whorls and the fine structure of the microtunnels along the breathing tube. We described the radula and penis morphology of five Dicharax species.